Making Chat at Home in the Hospital: Exploring Chat Use by Nurses - Karusala, Naveena; Wang, Ding; O'Neill, Jacki (CHI 2020, 2020)
In this paper, we examine WhatsApp use by nurses in India. Globally, personal chat apps have taken the workplace by storm, and healthcare is no exception. In the hospital setting, this raises questions around how chat apps are integrated into hospital work and the consequences of using such personal tools for work. To address these questions, we conducted an ethnographic study of chat use in nurses’ work in a large multi-specialty hospital. By examining how chat is embedded in the hospital, rather than focusing on individual use of personal tools, we throw new light on the adoption of personal tools at work—specifically what happens when such tools are adopted and used as though they were organisational tools. In doing so, we explicate their impact on invisible work (Star and Strauss, 1999) and the creep of work into personal time, as well as how hierarchy and power play out in technology use. Thus, we point to the importance of looking beyond individual adoption by knowledge workers when studying the impact of personal tools at work.